The Role Of Accounting Disclosure In Enhancing Solvency - Bali ,Mossab; Oubira, Mohamed Elsaid; Moussaoui, Amor (جامعة الوادي University of Eloued, 2024)
This study aims to explore the role of accounting disclosure in enhancing the relevance of financial statements and their appendices for the National Insurance Company. A questionnaire was distributed to collect information from a sample of 50 individuals from the study population, which includes both employed and independent accountants. The data were analyzed using the SPSS program. The study found that appropriate accounting disclosure has an impact on financial statements, particularly their appendices, by enhancing the relevance characteristic. The annually or periodically disclosed financial information contributes to future forecasting of the company's activities. Thecompany is committed to achieving relevance in financial statements in a way that aligns with the needs of information users, by providing timely, supported, and verified numerical financial disclosures. This assists in making decisions related to the company's future risks.
Keywords: Accounting Disclosure; Relevance; Financial Statements; Financial Information Users; National Insurance Company